2019
DOI: 10.1016/j.socscimed.2019.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the methods used in economic evaluations of targeted physical activity and sedentary behaviour interventions

Abstract: The burden of noncommunicable diseases (NCD) on health systems worldwide is substantial. Physical inactivity and sedentary behaviour are major risk factors for NCD.Previous attempts to understand the value for money of preventative interventions targeting physically inactive individuals have proved to be challenging due to key methodological challenges associated with the conduct of economic evaluations in public health. A systematic review was carried out across six databases (Medline, SPORTSDiscus, EconLit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…The inclusion criteria assessment resulted in ten systematic and one empirical (scoping) review (Fig. 1 ) [ 5 , 19 , 23 31 ] Excluded reviews are shown in Additional file 4 . Of the included reviews (Table 1 ), five addressed different preventive measures for older people [ 25 , 27 ] or children/adolescents [ 26 , 28 , 30 ], while the others targeted physical activity [ 23 ], implementation of DPHP [ 24 ], alcohol prevention [ 31 ], behavior change [ 5 ], injury prevention [ 29 ], or different areas of prevention [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria assessment resulted in ten systematic and one empirical (scoping) review (Fig. 1 ) [ 5 , 19 , 23 31 ] Excluded reviews are shown in Additional file 4 . Of the included reviews (Table 1 ), five addressed different preventive measures for older people [ 25 , 27 ] or children/adolescents [ 26 , 28 , 30 ], while the others targeted physical activity [ 23 ], implementation of DPHP [ 24 ], alcohol prevention [ 31 ], behavior change [ 5 ], injury prevention [ 29 ], or different areas of prevention [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 ) [ 5 , 19 , 23 31 ] Excluded reviews are shown in Additional file 4 . Of the included reviews (Table 1 ), five addressed different preventive measures for older people [ 25 , 27 ] or children/adolescents [ 26 , 28 , 30 ], while the others targeted physical activity [ 23 ], implementation of DPHP [ 24 ], alcohol prevention [ 31 ], behavior change [ 5 ], injury prevention [ 29 ], or different areas of prevention [ 19 ]. Overall, these reviews included 494 economic analyses (CEA: 42%, CUA: 20%, different types of economic study: 16%, CCA: 15%, CBA: 6%, CMA: 1%.…”
Section: Resultsmentioning
confidence: 99%
“…Complementary to previous reviews [8][9][10][11]14 , this is the first methodological review to provide an overview and critique of the modelling approaches used in model-based economic evaluations for estimating impacts of changes in PA on public health. This review has shed light on key structural assumptions that underlie the models, which can aid interpretation of the cost-effectiveness findings and highlights model development opportunities.…”
Section: Main Findingsmentioning
confidence: 99%
“…Several studies have reviewed the cost-effectiveness evidence for promoting physical activity (PA) in the general population and found the interventions to provide value for money in most cases [3][4][5][6][7] . However, methodological reviews have highlighted a number of challenges related to the economic evaluation of public health interventions, including PA [8][9][10][11] . Covering all elements of the evaluation, from research design of the intervention to the statistical and economic analyses, these challenges have previously been grouped into four broad categories: attribution of effects, measuring and valuing outcomes, intersectoral costs and consequences and incorporating equity concerns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation